2016
DOI: 10.1007/s10989-016-9551-7
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Down Regulates Apelin Gene Expression in Cardiac and Adipose Tissues of Insulin Resistant Diabetic Rats Fed by High-Calorie Diet

Abstract: Apelin is a newly discovered peptide that its serum level increases in diabetic patients with cardiovascular dysfunction. Recent studies indicate the beneficial actions of betaine in reducing the cardiovascular and metabolic complications, however data related to its effect on adipocytokine expression is limited. The aim of this study was to evaluate the effect of betaine supplementation on Apelin gene expression in cardiac muscle and adipose tissue of insulin resistance, diabetic rats fed by a high calorie di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…39,47,48 Nazari et al found that serum levels of apelin increased with insulin resistance in diabetic rats. 38 Dray et al demonstrated that apelin increased glucose uptake in isolated soleus muscles. They postulated that apelin's effects were mediated by the serine-threonine kinase AMPK in a pathway also involving eNOS.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…39,47,48 Nazari et al found that serum levels of apelin increased with insulin resistance in diabetic rats. 38 Dray et al demonstrated that apelin increased glucose uptake in isolated soleus muscles. They postulated that apelin's effects were mediated by the serine-threonine kinase AMPK in a pathway also involving eNOS.…”
Section: Dovepressmentioning
confidence: 99%
“…In clinical and experimental studies, serum level of apelin or its adipose tissue expression is increased in obese and insulin-resistant cases. [38][39][40] Apelin has a role in energy metabolism, improves the sensitivity of insulin in insulin-resistant obese mice, and it is related to increase in glucose uptake in skeletal muscle. 41 Studies have shown that CUR has a stronger antioxidant effect than vitamins E and C and can inhibit the activity of free radicals.…”
Section: Dovepressmentioning
confidence: 99%
“…Nutritional status can affect apelin in serum and a hypercaloric diet increases adipose tissue and plasma apelin concentrations [ 114 , 115 ]. Norvezh et al .…”
Section: Apelinmentioning
confidence: 99%
“…The rats (n = 60) were randomly divided into four equal groups (n = 15). Two groups were fed with high-energy diet [prepared by adding 20% sucrose (w/w) and 10% beef tallow (w/w) into diets] (Nazari et al, 2016) for 5 weeks and called High fat/High carbohydrate (HF/HC; n = 30); then, they received a single dose of streptozotocin (30 mg/kg, i.p; STZ, Sigma, Germany; Qian et al, 2015). Five days after STZ treatment, glucose was measured by hand-held glucometer (EasyGluco, South Korea) in HF/ HC.…”
Section: Experimental Designmentioning
confidence: 99%
“…Five days after STZ treatment, glucose was measured by hand-held glucometer (EasyGluco, South Korea) in HF/ HC. The elevation of serum glucose above 7.5 mmol/L was considered as an index and confirmation of diabetes induction (Nazari et al, 2016). One diabetic group (n = 15) received LC 300 mg kg −1 day −1 (Bazotte & Bertolini, 2012) in drinking water concomitant with HF/ HC diets for 28 days.…”
Section: Experimental Designmentioning
confidence: 99%